Management of the Use of Audio-Visual Media Based on Canva Application in Islamic Religious Education Subjects at Junior High Schools in Hamparan Perak District - Setiawan, Hasrian Rudi (Integrasi: Jurnal Studi Islam dan Humaniora, 2024)
The purpose of this research is to analyze the management of using audio-visual media based on Canva applications in Islamic Religious Education (IRE) at junior high schools in the Hamparan Perak district. This research employs a qualitative approach with descriptive methods, focusing on exploring how Canva-based audio-visual media is utilized and managed to improve students’ learning experiences and engagement in IRE classes. Data collection methods include interviews, observations, and documentation to gather insights from teachers and students. The findings indicate that the integration of Canva-based audio-visual media in IRE lessons positively impacts students’ understanding and engagement. Teachers noted that Canva’s flexibility allows them to design visually appealing, interactive, and relevant materials that resonate with students. Additionally, the study found that well-planned management of media use, including scheduling, preparation, and assessment of student responses, significantly enhances the effectiveness of learning. This research suggests that the adoption of Canva-based audio-visual media in IRE can be a valuable strategy to foster a more dynamic and interactive learning environment.